Pengaruh Produk Hijau dan Citra Merek terhadap Keputusan Pembelian Produk The Body Shop di Jember Melalui Kepercayaan - Anugrah Bayu Pratama (Fakultas Ekonomi dan Bisnis, 2024)
This research For analyze influence green product, and image brand to decision purchase The Body Shop products in Jember via trust . Internal data type study This is quantitative data . Data sources used in research This namely primary data from spread questionnaire . Retrieval technique sample in study This is purposive sampling with incidental sampling method , with total respondents as many as 170 consumers The Body Shop products . Deep data analysis study This is SEM-PLS with use tool SmartPLS data processing 4. Research results This ; 1) green products have an effect positive and significant to trust , 2) image brand influential positive and significant to trust , 3) green products no influential positive and significant to decision purchasing , 4) image brand influential positive and significant to decision purchase , 5) trust influential positive and significant to decision purchases , 6) green products have an effect positive and significant to decision purchase through trust , 7) image brand influential positive and significant to decision purchase through trust.
Entry oleh Arif 2026 Maret 25
Keywords: Green Product; Brand Image; Trust; Purchase Decision